Identification of SLIRP as a G Quadruplex-Binding Protein - Williams, Preston; Li, Lin; Dong, Xiaoli; Wang, Yinsheng (Journal of the American Chemical Society, 2017)
The guanine quadruplex (G4) structure in DNA is a secondary structure motif that plays important roles in DNA replication, transcriptional regulation, and maintenance of genomic stability. Here, we employed a quantitative mass spectrometry-based approach to profile the interaction proteomes of three well-defined G4 structures derived from the human telomere and the promoters of cMYC and cKIT genes. We identified SLIRP as a novel G4-interacting protein. We also demonstrated that the protein could bind directly with G4 DNA with K d values in the low nanomolar range and revealed that the robust binding of the protein toward G4 DNA requires its RRM domain. We further assessed, by using CRISPR-Cas9-introduced affinity tag and ChIP-Seq analysis, the genome-wide occupancy of SLIRP, and showed that the protein binds preferentially to G-rich DNA sequences that can fold into G4 structures. Together, our results uncovered a novel cellular protein that can interact directly with G4 DNA, which underscored the complex regulatory networks involved in G4 biology.